Analisis Manfaat Produk Tabungan Berencana Bank Syariah Indonesia dalam Mendukung Perencanaan Keuangan Keluarga - Agustin, Isnaini Faliha; Arifin, Sirajul (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the benefits of Bank Syariah Indonesia's Savings Plan product in supporting family financial planning. The method used is descriptive qualitative research, collecting primary data through interviews and secondary data through literature review. The research instruments were interview guidelines and reference documents related to the Savings Plan product. Data analysis was conducted through data reduction, presentation, and drawing conclusions based on field findings and literature. The results show that BSI Savings Plan offers various benefits, including assisting with short-term and long-term financial planning, fostering financial discipline, providing protection through sharia principles and insurance, and reducing family financial risks. This product also functions as a strategic instrument in improving family welfare while supporting the sustainability of household economic stability. Thus, BSI Savings Plan not only serves as a means of saving but also as a comprehensive solution for families in facing modern financial challenges.